1 PENGARUH PENGGUNAAN MASKER GAMBIR TERHADAP PERAWATAN KULIT WAJAH BERJERAWAT - Nasution, Suci Rahmawati; Rahmiati, Rahmiati; Rosalina, Linda (Journal of Home Economics and Tourism, 2017)
Acne cause pain, itching, and lack of confidence. To treat this abnormaly we used Gambir mask skin care cosmetics. This study aimed to analyze the use of Gambir mask to treat the acne, to the student of UNP with acne wits indicator color, shape, volume, and the amount of acne. This study used a quasi eksperimen methods with (Non Equivalent Control Group Design). The object of research is the papule acne type. UNP student population wits aged 17-25 years old who had acne, the technique of sampling through purposive sampling technique, with a sample size of 6 people. The collected data are primary data, descriptive analysis, hypothesis was tested by t (independent sampel t test). The study states that the control group (Xo) showed no significant change in the results, while the experimental group (X1) showed a significant change in results. Data are normal and homogeneous so that the t use Equal variances assumed. Price t count> t table (8.649> 2.074) it is proved that the hypothesis there is a difference significant influence on the use of the mask image in both groups against facial acne skin care is received at a significance level of 0,05 (5%).Keywords: gambir Mask, Facial skin care, acne